Environmental health and patient safety in indonesian sharia hospitals: A critical normative–empirical synthesis toward a maqasid-based governance framework - Dicky Budiman; Trisye Iverdina Ratnasari; Muji Mulyaningsih; Nyayu Firda (Sanitasi: Jurnal Kesehatan Lingkungan, 2026)
Sharia hospitals in Indonesia are rapidly evolving under Fatwa No. 107/DSN-MUI/X/2016 and MUKISI/SIRSMA standards; however, governance remains focused on contractual, financial, and halal compliance, leaving environmental health and patient safety underrepresented as measurable outcomes. This study synthesises normative and empirical evidence to assess the integration of these domains and proposes a maqasid al-shariah-based framework to render them operational. Utilizing a normative–empirical narrative synthesis, the research triangulated Indonesian regulatory and fatwa documents, certification standards, four domestic case studies, and comparative literature from Malaysia and Gulf countries. Results reveal that while environmental health and infection control are not entirely absent from current standards, their requirements remain fragmented across national accreditation and environmental regulations. Furthermore, case evidence highlights persistent gaps in halal supply chains, Sharia Supervisory Board engagement, and standardized safety indicators, whereas mature international models successfully embed these elements as core maqasid-linked components. Ultimately, Indonesian sharia healthcare governance possesses sufficient foundations to explicitly integrate environmental health and patient safety, where a unified maqasid-based indicator set would significantly enhance accountability, compliance, and overall safety performance.